Effect of Aralia chinensis on serum TNF-a, IL-4 and IL-10 level in rats with adjuvant-induced arthritis - Yi, Lei; Feng, Jianjun; Ji, Haiwang; Zhang, Xuechong (Bangladesh Journal of Pharmacology, 2012)
Our study investigated the effect of Aralia chinensis on serum tumor necrosis factor-α (TNF-α), Interleukins (IL-4, IL-10) in rats with adjuvant-induced arthritis. Adjuvant-induced arthritis rats had more slowly increased body weight, dramatically increased TNF-α level but reduced IL-4, IL-10 levels compared with control group. A. chinensis, Tripterygium wilfordii and control group had significantly increased body weight, IL-4, IL-10, and markedly reduced arthritis index and TNF-α level compared with the adjuvant-induced arthritis group. A. chinensis and T. wilfordii group had significantly increased IL-4 and IL-10 levels and markedly reduced TNF-α level compared with control group. A. chinensis could significantly increase the IL-4 level compared with the control group and it can balance the cytokines in arthritis rats, which attributes to the improvement of adjuvant induced arthritis.